Structural and Mechanical Properties of Cubic Silicon Nitride: A Molecular Dynamics Study - Thao, Nguyen Thi; Ha, Nguyen Thi Thanh; Van Vinh, Le (VNU Journal of Science: Mathematics - Physics; Vol 38 No 3, 2022)
Abstract: The molecular dynamics simulations have been used to study the microstructure as well as mechanical behavior of cubic silicon nitride (c-Si 3 N 4 ) under the extended deformation. The silicon nitride sample was simulated under the cooling process and high pressure. At T=300 K, dominant nitrogen (N) atoms arrange into fcc lattice, and the rest of N atoms have hexagonal close-packed (hcp) and disordered structures. The hcp and disordered N atoms gather into the narrow bands. The phonon spectra of this sample are calculated and discussed. In this work we also present a molecular dynamics prediction for the elastic moduli in strained cubic silicon nitride as functions of the volumetric strain. Young’s modulus and Poisson’s ratio are also calculated for the  c-Si 3 N 4 .